Replicative history marks transcriptional and functional disparity in the CD8 + T cell memory pool - Bresser, Kaspar; Kok, Lianne; Swain, Arpit C; King, Lisa A; Jacobs, Laura; Weber, Tom S; Perié, Leïla; Duffy, Ken R; de Boer, Rob J; Scheeren, Ferenc A; Schumacher, Ton N (Nature immunology, 2022)
Clonal expansion is a core aspect of T cell immunity. However, little is known with respect to the relationship between replicative history and the formation of distinct CD8 memory T cell subgroups. To address this issue, we developed a genetic-tracing approach, termed the DivisionRecorder, that reports the extent of past proliferation of cell pools in vivo. Using this system to genetically 'record' the replicative history of different CD8 T cell populations throughout a pathogen-specific immune response, we demonstrate that the central memory T (T ) cell pool is marked by a higher number of prior divisions than the effector memory T cell pool, owing to the combination of strong proliferative activity during the acute immune response and selective proliferative activity after pathogen clearance. Furthermore, by combining DivisionRecorder analysis with single-cell transcriptomics and functional experiments, we show that replicative history identifies distinct cell pools within the T compartment. Specifically, we demonstrate that lowly divided T cells display enriched expression of stem-cell-associated genes, exist in a relatively quiescent state, and are superior in eliciting a proliferative recall response upon activation. These data provide the first evidence that a stem-cell-like memory T cell pool that reconstitutes the CD8 T cell effector pool upon reinfection is marked by prior quiescence.